The Human Cytomegalovirus Fc Receptor gp68 Binds the Fc C(H)2-C(H)3 Interface of Immunoglobulin G - Sprague, Elizabeth R. (American Society for Microbiology (ASM), 2008)
Recognition of immunoglobulin G (IgG) by surface receptors for the Fc domain of immunoglobulin G (Fcγ), FcγRs, can trigger both humoral and cellular immune responses. Two human cytomegalovirus (HCMV)-encoded type I transmembrane receptors with Fcγ-binding properties (vFcγRs), gp34 and gp68, have been identified on the surface of HCMV-infected cells and are assumed to confer protection against IgG-mediated immunity. Here we show that Fcγ recognition by both vFcγRs occurs independently of N-linked glycosylation of Fcγ, in contrast with the properties of host FcγRs. To gain further insight into the interaction with Fcγ, truncation mutants of the vFcγR gp68 ectodomain were probed for Fcγ binding, resulting in localization of the Fcγ binding site on gp68 to residues 71 to 289, a region including an immunoglobulin-like domain. Gel filtration and biosensor binding experiments revealed that, unlike host FcγRs but similar to the herpes simplex virus type 1 (HSV-1) Fc receptor gE-gI, gp68 binds to the C(H)2-C(H)3 interdomain interface of the Fcγ dimer with a nanomolar affinity and a 2:1 stoichiometry. Unlike gE-gI, which binds Fcγ at the slightly basic pH of the extracellular milieu but not at the acidic pH of endosomes, the gp68/Fcγ complex is stable at pH values from 5.6 to pH 8.1. These data indicate that the mechanistic details of Fc binding by HCMV gp68 differ from those of host FcγRs and from that of HSV-1 gE-gI, suggesting distinct functional and recognition properties.